Ketoprofen hypersensibility and idiosyncratic response – a case report. (3rd March 2020) - Araujo, Marcio Antonio Rodrigues
Abstract: Context: Ketoprofen is widely used to remove pain. A steady increase on allergic reactions and photoallergic contact dermatitis related to ketoprofen has been reported when there is topical use. However, there are few documented cases of hypersensitivity when it is administered systemically. Objective: Present a case of hypersensitivity reaction after systemic administration of ketoprofen for pain control in nephritis crisis. Case description: A 43-years-old Caucasian man diagnosed with renal colic (kidney lithiasis), who was initially treated with 100 mg of tramadol (IV), followed by 4 mg of thiocolchicoside (IM) which caused no relief. Then 100 mg of ketoprofen was administered (IV). Right after the patient began to show hypersensitivity reaction type I characterized by intense coughing, rhinitis, angioedema, periorbital edema, rash, and scleral jaundice. Discussion and conclusion: Maybe it was a case of drug-induced liver disease, however therapeutic dosages of all administered drugs only once. The mechanisms involved were not investigated, but may be the result of allergic and immunologic aspects caused by ketoprofen and facilitated by a history of hypersensitivity to other NSAIDs as reported by the patient. As for jaundice can be attributed to drug toxicity since laboratory parameters did not reveal any evidence of liver disease.